O gênero textual meme : práticas de leitura e produção textual para atribuição de sentido às múltiplas semioses - Matos, Manoel Rodrigues de Abreu (2019)
This research presents a proposal of pedagogical intervention developed in an 8th grade class of Elementary School in the municipal school on Olindina city- BA. With this, it was aimed, start of the realization with six workshops aimed to the reading and memes production, the expansion of the multiliteracies for the meaning of the multiple semioses present in the multimodal texts. The memes SHIFMAN, 2014) constitute an accessible, cheap and fun way to the political participation of the individuals in the context of the web, reducing passivity in the face of social facts. In this sense, the methodology adopted in this work is the action research in terms of Thiollent (2012) because it is an intervention to solve a diagnosed problem, in this case, the expansion of multiliteracies. This research is based on the guidelines of Cope and Kalantzis (2000), Rojo (2012) and Oliveira (2013) on multimodality and multiliteracies; Paviani and Fontana (2009), about workshops; Leurquin (2014), Dolz, Noverraz and Schneuwly (2011), about didactic sequence; Koch, Bentes and Cavalcante (2012), regarding intertextuality; Marcuschi (2011) and Miller (2012), on textual genres and Braga (2013), on digital literacy. At the end of the application of this proposal, it was observed that there were improvements regarding in the reading and memes production. The students came to perceive and to signify the semioses and intertexts, that facilities the understanding of the messages conveyed, be it reading or production. The learning obtained with memes, regarding the meaning of the semiosis, can be applied to other texts, possibiliting an effective and critical participation in the socio-cultural practices of daily life.